2022
DOI: 10.1126/scitranslmed.aaz6280
|View full text |Cite
|
Sign up to set email alerts
|

The small-molecule SMARt751 reverses Mycobacterium tuberculosis resistance to ethionamide in acute and chronic mouse models of tuberculosis

Abstract: The sensitivity of Mycobacterium tuberculosis , the pathogen that causes tuberculosis (TB), to antibiotic prodrugs is dependent on the efficacy of the activation process that transforms the prodrugs into their active antibacterial moieties. Various oxidases of M. tuberculosis have the potential to activate the prodrug ethionamide. Here, we used medicinal chemistry coupled with a phenotypic assay to select the N-acylated 4-phenylpiperidine compound series. The lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Recently, Willand, Baulard, et al discovered a small molecule SMARt751 that potentiated the efficacy of ethionamide (ETH) against a panel of resistant M. tuberculosis both in vitro and in vivo . Elegant mode of action studies demonstrated that SMARt751 promoted the production of MymA via inhibition of a cryptic negative transcriptional regulator . To date, these systems have received only limited attention.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Willand, Baulard, et al discovered a small molecule SMARt751 that potentiated the efficacy of ethionamide (ETH) against a panel of resistant M. tuberculosis both in vitro and in vivo . Elegant mode of action studies demonstrated that SMARt751 promoted the production of MymA via inhibition of a cryptic negative transcriptional regulator . To date, these systems have received only limited attention.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, INH is activated by the peroxidase KatG. Both enzymes form a stable covalent adduct with nicotinamide adenine dinucleotide (NAD) 46 that inhibits InhA, which is involved in mycolic acid biosynthesis. 37,45,47,48 As DA-CB may also inhibit mycolic acid biosynthesis, we investigated the cellular processes that DA-CB alters by employing a multi-omics approach to characterize the metabolome, proteome, and lipidome of Msm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In contrast, INH is activated by the peroxidase KatG. Both enzymes form a stable covalent adduct with nicotinamide adenine dinucleotide (NAD) that inhibits InhA, which is involved in mycolic acid biosynthesis. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…The old antibiotic ETH, which was used for a long time to treat drug-resistant TB [ 1 ], is benefiting from a renewal since the development of new compounds boosting its activity in vivo [ 24 , 25 ] are currently being assessed in a Phase 1 trial (ClinicalTrials.gov n° NCT04654143).…”
Section: Discussionmentioning
confidence: 99%